1993
DOI: 10.1007/bf00015979
|View full text |Cite
|
Sign up to set email alerts
|

A light- and developmentally-regulated DNA-binding interaction is common to the upstream sequences of the wheat Calvin cycle bisphosphatase genes

Abstract: We have characterised a DNA-binding interaction common to the upstream sequences of the wheat fructose-1,6-bisphosphatase (FBPase) and sedoheptulose-1,7-bisphosphatase (SBPase) genes. The recognition site for this sequence-specific binding activity, designated wheat FBPase factor (WF-1), is located within 125 bp of the transcription start site of each gene. Within these regions there are no sequence motifs similar to those shown to be important for light-regulated expression in other species. The binding activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…The regulation of SBPase gene expression is likely to be largely at the level of transcription, as is the case for the nuclear encoded Rubisco small subunit genes (Dean et al 1989). The wheat and Arabidopsis SBPase genes both contain a number of DNA sequence motifs which have been identified as having a role in the transcriptional regulation of other photosynthetic genes (Miles et al 1993; Willingham et al 1994). The upstream sequence of the Chlamydomonas SBPase gene also contains elements important for directing light‐regulated expression (Hahn et al 1998).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The regulation of SBPase gene expression is likely to be largely at the level of transcription, as is the case for the nuclear encoded Rubisco small subunit genes (Dean et al 1989). The wheat and Arabidopsis SBPase genes both contain a number of DNA sequence motifs which have been identified as having a role in the transcriptional regulation of other photosynthetic genes (Miles et al 1993; Willingham et al 1994). The upstream sequence of the Chlamydomonas SBPase gene also contains elements important for directing light‐regulated expression (Hahn et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…The upstream sequence of the Chlamydomonas SBPase gene also contains elements important for directing light‐regulated expression (Hahn et al 1998). However, as yet only one putative transcription factor, WF‐1, present in wheat leaf nuclei, has been identified as interacting with an SBPase gene upstream sequence (Miles et al 1993).…”
Section: Introductionmentioning
confidence: 99%
“…In plants, the expression of the SBPase gene is mainly regulated by light, developmental stage, and glucose regulation [ 15 , 45 , 46 ] and is tissue-specific [ 18 ]. This study found that the GhSBPase gene was specifically highly expressed in leaves and expressed at low levels or was absent in other tissues, indicating that the GhSBPase gene may play an important role in photosynthesis in cotton leaves.…”
Section: Discussionmentioning
confidence: 99%
“…The FBPase gene originated in bacteria in conjunction with the endosymbiotic event giving rise to mitochondria, and widely distributed in bacteria, fungi, higher plants and animals [ 29 ]. FBP genes have been identified and analyzed in many plants, such as potato [ 30 , 31 ], wheat [ 32 , 33 ], pea [ 34 , 35 , 36 ], spinach [ 37 ], tomato [ 38 ], A. thaliana [ 39 ], Porteresia coarctata [ 40 ], P. haitanensis [ 17 ], Euglena gracilis [ 41 ], P. massoniana [ 18 ] and others. To date, the genome-wide analysis of the FBP gene family has not been reported in forestry trees.…”
Section: Discussionmentioning
confidence: 99%